The VOLUME OF FOREIGN TRADE IN SERBIA AND NORTH MACEDONIA - Kisin, Jovana; Ignajtović, Jelena; Mashovic , Azemina (Poslovna ekonomija, 2023)
The Western Balkans region has directed its economic growth and development through the integration of national economies into international trade flows. Given that all countries in the region have faced the consequences of the Covid-19 pandemic, the overall situation has also affected foreign trade relations. Although the European Union is the largest trade partner of the countries in the region in recent decades, the presence of the People’s Republic of China and its influence on the region’s trade is becoming more and more noticeable. The aim of this paper is to analyze the state of foreign trade in the case of Serbia and North Macedonia. as the countries of the Western Balkans region and to point out the directions of future trade relations in the case of these two countries. The research is based on descriptive data analysis in the period 2010-2020. while the data used are available in international and domestic statistical databases. The paper consists of three chapters. After the introduction, the first chapter analyzes the dynamics of foreign trade in the Western Balkans. The second chapter is based on the analysis of the trend of foreign trade in Serbia, while the third chapter analyzes the trend of foreign trade in North Macedonia. Finally, concluding remarks are given. The results of the research showed that the current state of foreign trade was greatly affected by the pandemic crisis, but that the perspectives are mainly focused on increasing trade with the EU and China. Although in 2020, there was a decline in economic activity and a slowdown in global trade, the value of foreign trade in these countries has increased, but with the growth of the foreign trade deficit.